Account in Murder on the Orient Express Movie Script - Sigit Apriandi Sigit (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2016)
This research aims to find out how Account is described by 12 characters in Murder on the Orient Express Movie script on Justification and Excuses aspects. The researcher used descriptive qualitative as a research method. The source of data in this research was taken from primary data, namely the script for the film Murder on the Orient Express by Agatha Christie and Michael Green which was taken from www.scripts.com and secondary data were taken from audiovisual in the film Murder on the Orient Express. The researcher collected data by downloading, reading, watching, and coding the data. The data analysis technique was done by presenting, describing, interpreting, and concluding the results of this research. The results of this research indicate that account is actually applied by the antagonists to avoid being accused of being the killer of one of the train passengers. The researcher found 11 data containing elements of Account, which included aspects of Justification and Excuses. In Excuses, the accident aspect is the most dominant because this murder is based on past events, then the scapegoating aspect is accusing other people of doing the act so as not to be accused and the Defeasibility aspect is the last factor that causes Account’s behavior in this Movie script.